Low-energy light bulbs, computers, tablets and the blue light hazard - O'Hagan, J B (Eye (Lond), 2016)
The introduction of low energy lighting and the widespread use of computer and mobile technologies have changed the exposure of human eyes to light. Occasional claims that the light sources with emissions containing blue light may cause eye damage raise concerns in the media. The aim of the study was to determine if it was appropriate to issue advice on the public health concerns. A number of sources were assessed and the exposure conditions were compared with international exposure limits, and the exposure likely to be received from staring at a blue sky. None of the sources assessed approached the exposure limits, even for extended viewing times.